Luck, love & lemon pie : a novel - Reichert, Amy E., 1974- (Gallery Books, 2016)
"When Milwaukee wife and mother M.J. Boudreaux realizes that her husband Chris seems more interested in spending time at the casino than he does with her, she seeks out an activity that they can do together to reignite their flame, and it seems that poker is her best bet. Although it doesn't give her the quality time with Chris that she'd hoped, M.J. finds she has a natural knack for the game. Increasingly unhappy at home, she turns to the felt of the poker table for escape. As she spends more time at the tables and less with her family, freedom becomes intoxicating and starts to fill a hole in MJ's life she didn't realize was there. For the first time in years, she's carving out a place for herself outside her roles of wife and mother. After winning a poker tournament, M.J. finds herself enjoying her prize of a trip to Vegas, living the life of a poker hotshot drinks, dancing, and attracting the attention of a certain magnetic poker star. But when she's forced to choose between her family and her new glamorous lifestyle, M.J. realizes the stakes may be higher than she thought"--